Antioxidantes artificiales en la industria alimentaria - Alvines Davalos, Alejandra Fiorella (2019)
The objective of this work was to present the latest research related to the consumption of Artificial Antioxidants present in food. The most commonly used antioxidants are BHT, TBHQ, BHQ, E310, citric acid and EQ. Artificial Antioxidants can generate imbalance with the oxidative system, among other cardiovascular, cancer, gastric, respiratory, neurological and endocrine diseases. The consumption of antioxidants in the permitted dose minimizes the risk of intoxication